The Contribution Of Digital Transformation Governance To Enhancing The Reliability Of Financial Reports: An Analytical Study Of The Opinions Of A Sample Of Employees In The Accounting, Auditing, And Internal Control Departments At The General Directorate - saif ALI (Indonesian Journal Publisher, 2026)
This research aims to explore the contribution of digital transformation governance to enhancing the reliability of financial reports. This is achieved through an analytical study of the opinions of a sample of employees in the accounting, auditing, and internal control departments of the General Directorate of Education in Al-Qadisiyah, with a sample size of (50) individuals. The research problem lies in the need to enhance the quality and reliability of financial reports in light of digital transformation applications. The problem is formulated through the main question: What is the contribution of digital transformation governance to enhancing the reliability of financial reports? The research included two main variables: the independent variable, digital transformation governance, consisting of six dimensions (relevance and appropriateness, truth and integrity, ease of understanding, timeliness, credibility, and comparability), and the dependent variable, the reliability of financial reports. A one-dimensional scale consisting of (10) items was adopted. To achieve the research objectives, the descriptive-analytical method was used, relying on a questionnaire to collect data on the study variables. The data were analyzed using various statistical methods, including the arithmetic mean, standard deviation, and Pearson correlation coefficient, using the statistical software (SPSS.v29 and AMOS.v29). The preliminary results showed a positive and statistically significant relationship between digital transformation governance and the reliability of financial reports, indicating that strengthening the six dimensions of digital governance contributes to raising the level of reliability of financial information in the two sections of the research sample.